Daughter of Fortune : A Novel - Allende, Isabel (New York : HarperCollins, 1999)
A Chilean woman searches for her lover in the goldfields of 1840s California. Arriving as a stowaway, Eliza finances her search with various jobs, including playing the piano in a brothel.
Keywords: Gold mines and mining -- California; Fiction; California -- History -- 1846-1850; Fiction; California -- Social life and customs -- 19th century; Fiction